Telerehabilitation Policy Report: Interprofessional Policy Principles and Priorities - Evelyn Abrahante Terrell; Andy Bopp; Kristen Neville; David Scala; Kyle Zebley (International Journal of Telerehabilitation, 2021)
The American Occupational Therapy Association, the American Physical Therapy Association, the American Speech-Language-Hearing Association and the American Telemedicine Association are collaborating to advance telehealth and ensure sustainability of virtual care services beyond the COVID-19 pandemic. These professional associations represent the interests of more than 888,000 rehabilitation services professionals. This paper summarizes the current state of telehealth policy principles and priorities for rehabilitation services. The report outlines key considerations when advocating with policymakers to avoid the “Telehealth Cliff” for audiology and therapy services and to facilitate the continued advancement of telehealth innovation and transformation by rehabilitation services professionals.